1998
DOI: 10.1897/1551-5028(1998)017<0806:roahrm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Aryl Hydrocarbon Receptor-Mediated Activity of Polychlorinated Biphenyl Mixtures Due to Anaerobic Microbial Dechlorination

Abstract: Aroclors 1242 and 1254 were anaerobically dechlorinated by microorganisms eluted from polychlorinated biphenyl (PCB)-contaminated River Raisin (RR) and Silver Lake (SL) sediments. Dechlorination occurred primarily from the meta positions. H4IIE rat hepatoma cell bioassays for ethoxyresorufin-O-deethylase (EROD) induction potency, a measure of aryl hydrocarbon receptor-mediated toxic potential, revealed that the potencies of the Aroclors were considerably reduced after dechlorination. The decreases in EROD indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
0
30
2
2
Order By: Relevance
“…The reason for these different results lies in the fact that the biological activities measured previously were mediated by coplanar congeners but those measured in our study involve noncoplanar and lightly chlorinated congeners [21]. Clearly, the conversion of Aroclors by anaerobic dechlorination to product mixtures containing a higher fraction of more lightly chlorinated, ortho-substituted congeners produces a loss of Ah-receptor-mediated activities [4] because of the loss of coplanar congeners with chlorine in the meta and para positions in the biphenyl molecule [2]. In contrast, no loss or, in certain cases, a gain in the biological activity in the product mixtures can be attributed to the predominance of noncoplanar and lightly chlorinated congeners.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The reason for these different results lies in the fact that the biological activities measured previously were mediated by coplanar congeners but those measured in our study involve noncoplanar and lightly chlorinated congeners [21]. Clearly, the conversion of Aroclors by anaerobic dechlorination to product mixtures containing a higher fraction of more lightly chlorinated, ortho-substituted congeners produces a loss of Ah-receptor-mediated activities [4] because of the loss of coplanar congeners with chlorine in the meta and para positions in the biphenyl molecule [2]. In contrast, no loss or, in certain cases, a gain in the biological activity in the product mixtures can be attributed to the predominance of noncoplanar and lightly chlorinated congeners.…”
Section: Discussioncontrasting
confidence: 71%
“…Coplanar congeners act primarily through binding to the Ah-receptor, in contrast to noncoplanar congeners, which act by increasing intracellular free calcium and activating signal-transduction pathways through mechanisms not yet completely understood [10,[17][18][19][20]. Whereas previous reports indicated a loss of PCB-related inhibition of in vitro fertilization [3] and induction of CYP1A1 activity [4] occurred when product mixtures identical to those used in the present study were evaluated, our results indicate no loss of biologic activity when two different cellular functions were examined. The reason for these different results lies in the fact that the biological activities measured previously were mediated by coplanar congeners but those measured in our study involve noncoplanar and lightly chlorinated congeners [21].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Intestinal microbes or enzymes are also capable of debrominating PBDEs in carp and probably in other fish species (Stapleton et al 2004c). It has been observed that microbes preferably dehalogenate polybrominated and polychlorinated biphenyls from the meta-and parapositions, whereas the halogen substituents in the ortho-position are more recalcitrant (Bedard and Van Dort 1998;Quensen et al 1998). Some evidence also exists for preferential meta-debromination (positions 3 and 5) and selective accumulation of certain PBDE congeners in fish.…”
Section: Introductionmentioning
confidence: 99%
“…First, microbial reductive dechlorination in sediments, together with reduced input of PCBs and associated dilution by deposition of cleaner sediment, may lead to a gradual decline of dioxin-like toxicity of PCB mixtures [10][11][12]. Microbial reductive dechlorination of PCBs in anaerobic sediments is an important environmental transformation [13,14].…”
Section: Introductionmentioning
confidence: 99%